The evolution of web through time - Dixit, Pradhyumn (International Journal of Emerging Trends in Science and Technology, 2022)
We utilize web 2.0 in today’s atmosphere to access and update information on the internet. In today’s society, we use websites and web applications to do jobs more quickly. Web development has introduced new opportunities as well as new obstacles to web-based education and learning. The first version of the web, Web 1.0, was a static (read-only) medium, whereas Web 2.0 is a Read/Write medium. Web 3.0, the most current and still-evolving version of the web, is now a technologically advanced medium that allows us (users) to read, write, and execute, as well as robots to conduct some of the intellectual thinking once reserved for humans.